Ingresos y egresos de la Empresa Davosi S.A del cantón Vinces del primer semestre del año 2024. - Carpio Gurumendi, Gloria Yomira (2024)
This case study was developed in the company Davosi S.A. of the Vinces canton of the province of Los Ríos, which faces a direct problem in its income and expenses due to its main factor being the imbalance in banana prices. The main objective of this research is to identify the factors that influence the variation in income in the first half of 2024. This study was carried out with a mixed approach, that is, a qualitative and quantitative approach that helped collect textual and numerical data that served to argue for this research. In turn, techniques and instruments related to the interview and survey were used, together with the application of a vertical analysis to the income statement for the first half of 2024. Income showed a constant decrease due to the type of contract signed for this year, which consisted of a variable price. The variation in prices was demonstrated, which culminated in June with a decrease of 26%. In addition, within its expenses represented in the income statement, it presents 74% of production costs of 100% of sales, with direct labor and materials used being the items with the greatest influence within the expenses of the company Davosi S.A. Consequently, the company obtains after costs 26% of income for each dollar of sales, despite the factors that this economic sector faces, the company generated 14% of net profit of 100% of the income, which allows it to remain in the market facing new challenges looking for new investment opportunities that allow it to continue growing.